2011
DOI: 10.1038/cdd.2011.143
|View full text |Cite
|
Sign up to set email alerts
|

A set of miRNAs participates in the cellular senescence program in human diploid fibroblasts

Abstract: Here we show that replicative senescence in normal human diploid IMR90 fibroblasts is accompanied by altered expression of a set of microRNAs (miRNAs) (senescence-associated miRNAs), with 14 and 10 miRNAs being either up or downregulated (42-fold), respectively, in senescent with respect to young cells. The expression of most of these miRNAs was also deregulated upon senescence induced by DNA damage (etoposide) or mild oxidative stress (diethylmaleate). Four downregulated miRNAs were part of miRNA family-17, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
109
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(118 citation statements)
references
References 38 publications
8
109
1
Order By: Relevance
“…Expression profiling of microRNAs (miRNAs, a class or regulatory RNAs responsible for posttranscriptional gene silencing by either degrading the target mRNA or preventing its translation) have revealed that these genes can function as either tumor suppressors or oncogenes in human tumors. Several studies have revealed that a variety of miRNAs are also differentially regulated during replicative senescence of human fibroblasts; [67][68][69][70] importantly, senescent fibroblasts appear to express distinct collections of miRNAs that play a central role in the senescence-elicited tumor suppression. 71 Because miRNAs extensively studied in the EMT of cancer cells (e.g., miR-200 family) [72][73][74][75] have recently been involved in the oxidative stress signature that regulates cellular senescence and tumorigenesis, 76,77 we decided to survey whether EMT-related miRNAs were differentially expressed in dividing (early-passage) HDFs compared with late-passage fibroblasts that had suffered an accelerated replicative senescence due to chronic exposure to metformin.…”
Section: Resultsmentioning
confidence: 99%
“…Expression profiling of microRNAs (miRNAs, a class or regulatory RNAs responsible for posttranscriptional gene silencing by either degrading the target mRNA or preventing its translation) have revealed that these genes can function as either tumor suppressors or oncogenes in human tumors. Several studies have revealed that a variety of miRNAs are also differentially regulated during replicative senescence of human fibroblasts; [67][68][69][70] importantly, senescent fibroblasts appear to express distinct collections of miRNAs that play a central role in the senescence-elicited tumor suppression. 71 Because miRNAs extensively studied in the EMT of cancer cells (e.g., miR-200 family) [72][73][74][75] have recently been involved in the oxidative stress signature that regulates cellular senescence and tumorigenesis, 76,77 we decided to survey whether EMT-related miRNAs were differentially expressed in dividing (early-passage) HDFs compared with late-passage fibroblasts that had suffered an accelerated replicative senescence due to chronic exposure to metformin.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the set of miRNAs with reduced expression during DGCR8-mediated arrest are also downregulated during oncogeneinduced senescence (Fig. 4A), replicative senescence (Bonifacio & Jarstfer, 2010;Marasa et al, 2010;Wang et al, 2011;Faraonio et al, 2012) or DNA-damage induced senescence (Greussing et al, 2013) in different strains of human primary fibroblasts. In addition, some of these miRNAs have been shown to bypass oncogene-induced senescence in human fibroblasts or epithelial cells (Voorhoeve et al, 2006;Borgdorff et al, 2010; and are overexpressed in tumors (Ivanovska et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Progress has been made in this regard in C. elegans by observing alterations in lifespan of lin-4, mir-71 and other mutants (Boehm and Slack, 2005;de Lencastre et al, 2010). Additionally, it has recently been shown that overexpression of several miRNAs that are upregulated during cellular senescence results in the formation of characteristic features of senescent cells (Faraonio et al, 2011). Nevertheless, studies in mammalian models that constitutively or conditionally lack or overexpress miRNAs will provide compelling evidence for any conserved aging mechanism mediated by miRNAs.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…The miR-17-92 cluster, along with its paralogous clusters miR106a-363 and miR-106b-25, regulate cellular senescence and are all downregulated in several aging models, whereas they are all upregulated in some cancers (Faraonio et al, 2011;. These miRNAs target PTEN, and it is thought that their downregulation during aging causes an increase in PTEN levels, which results in suppression of the IIS pathway (Fig.…”
Section: Iis and Mir-17-92mentioning
confidence: 99%